The degradation of plastics (cars) / Saiful Bakhtiar Abdullah, Ahmad Shaiful Mazran Mohammad and Noor Edzwan Hishamuddin Sadarudin - Abdullah, Saiful Bakhtiar; Mohammad, Ahmad Shaiful Mazran; Sadarudin, Noor Edzwan Hishamuddin (Faculty of Mechanical Engineering, 2001)
The development of modem cars industries owes much to the technological improvement made in the material of the cars component over many years. This report is about the study made on degradation of polymers in automotive. The study has been concentrated on the polymer components their usage, properties, selection, factors and the advantages and disadvantages of polymer. It also includes looking at polymer degradation after a certain period and factors that involved such as chemical and UV light. Information gathered from automotive related industries on polymer components helped to clarify some of unknown facts about polymer degradation. It will provide some information for the industries to used in their production and polymer used.